Entrepreneurial Leadership and Innovative Work Behavior: The Role of Creative Self-efficacy - Endi Sarwoko (Universitas Hayam Wuruk Perbanas, 2020)
Several previous studies have tested the relationship between leadership type and innovative work behavior. However, there have been only a few empirical studies examining the mediating role of creative self-efficacy on the relationship between entrepreneurial leadership and innovative work behavior. This study was conducted to fill this gap to understand the relationship between entrepreneurial leadership and innovative work behavior and the role of creative self-efficacy as a mediating variable for the relationship between entrepreneurial leadership and innovative work behavior. Data were collected using a questionnaire distributed to 190 employees of the Astra Honda Authorized Service Station (AHASS) and analyzed using Structural equation modeling with SmartPLS software. The results indicate that entrepreneurial leadership increases the innovative work behavior of employees. Besides, entrepreneurial leadership increases creative self-efficacy and leads to increased employee innovative work behavior. This study contributes to the development of the literature by providing empirical evidence on the relationship between entrepreneurial leadership and innovative work behavior and the role of creative self-efficacy in innovative behavior. This study confirms Social Cognitive Theory (SCT) that a person's self-efficacy will generate creative ideas in the workplace and produce innovative work. The practical implication is that leaders must provide greater opportunities for employees to develop creative ideas in the workplace to achieve an increase in innovative work behavior.